Transcriptomic analysis of reproductive organs of pregnant mice post toxoplasma gondii infection reveals the potential factors that contribute to poor prognosis - Deng, Meng-Ling; Chen, Jun-Rong; Yang, Jian-Fa; Ma, Jun; Shu, Fan-Fan; Zou, Feng-Cai; He, Jun-Jun (Frontiers in Microbiology, 2024)
Toxoplasma gondii is an obligate intracellular parasite of phylum Apicomplexa that poses a huge threat to pregnant hosts, and induces tragic outcomes for pregnant hosts, fetuses and newborns. However, the molecular mechanism underlying the tragic consequences caused by T. gondii remains to be revealed. In the present study, we applied RNA-seq to study the transcriptomic landscape of the whole reproductive organ of pregnant mice post T. gondii infection, aiming to reveal the key altered biological characters of reproductive organs of pregnant mice that could contribute to the tragic outcomes caused by T. gondii infection. The results of the present study showed that the transcriptome of reproductive organs of pregnant mice was significantly altered by T. gondii infection. A total of 2598 differentially expressed genes (DEGs) were identified, including 1449 upregulated genes and 1149 downregulated genes. Enrichment analysis of the DEGs showed that the significantly altered features of reproductive organs of pregnant mice were excessive inflammatory responses, downregulated metabolism processes, and congenital diseases. The chemotaxis of immune cells in the reproductive organs of infected pregnant mice could also be reshaped by 19 differentially expressed chemokines and 6 differentially expressed chemokine receptors that could contribute to the damages of reproductive organ in pregnant mice. Overall, the findings of present study may help to understand the pathogenic mechanism of the acute T. gondii infection in reproductive organs of pregnant mice, and it could also help to improve toxoplasmosis therapeutics for pregnant individuals.